Designing for Efficiency: Examining the Impact of Centralized and Decentralized Nurse Stations on Interdisciplinary Care Processes. (June 2020) - Fay, Lindsey; Santiago, Joshua E.; Real, Kevin; Isaacs, Kathy
Abstract : OBJECTIVE: This study examined the impact of centralized and decentralized unit designs on an interdisciplinary team's perceptions of efficiency through the use of a preoccupancy and postoccupancy evaluation of a cardiovascular unit. BACKGROUND: During the premove study, the service line was housed across 4 separate locations, each with a centralized nurses' station. The postmove design was housed on 1 floor with decentralized stations. METHODS: For this qualitative study, 14 focus groups and 1 interview were conducted. Analysis of the data was guided by a developed framework for efficiency classified into 7 categories. RESULTS: Outcomes reveal that efficiency was impacted by issues including walking, access to supplies and equipment, proximity to staff, and overall unit configuration and size. CONCLUSIONS: Although the design of the decentralized unit positions staff members closer to patients, many feel isolated while the centralized units seemed to better promote staff proximity and access to supplies.